Modality to promote the introduction of new technology into production, businesses - Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This article pointed out various modalities to promote the application of scientific research and technological development achievements in production and businesses. The author had systemized sequential activities related to the process of technology development and promotion of new technologies commercialization in order to provide basic knowledge in systematic way and measures to increase the likelihood of success in the introduction of new technologies into production and businesses. Code: 15041401